The Nexus between Financial Crisis and Household Consumption: Evidence from Emerging Countries - Dhrifi, Abdelhafidh (Journal of Social Economics Research, 2014)
This paper stains to test the effects of financial crisis on household consumption. More specifically, an aggregate annual data from 36 emerging countries from 1990-2012, is used to estimate a model that capture the interrelationship between financial crisis and household consumption. Our findings show that emerging countries that have experienced ﬁnancial crisis during the last three decades tend to experience a substantially greater contraction of their consumption level. Whatever the type of crisis considered, they are generally followed by a substantial contraction of their welfare. More specifically, banking crisis, in contrast to the currency ones, appears to have a more important impact on the standard living household. On the other hand, twin crisis seems to have a more pronounced impact than the two first ones.